1982
DOI: 10.1021/bi00256a001
|View full text |Cite
|
Sign up to set email alerts
|

Proton gradient linkage to active uptake of [3H]acetylcholine by Torpedo electric organ synaptic vesicles

Abstract: It has been confirmed that cholinergic synaptic vesicles isolated from the electric organ of Torpedo californica exhibit adenosine 5'-triphosphate (ATP) dependent active uptake of [3H]acetylcholine. Active uptake can be completely inhibited by low concentrations of the mitochondrial uncouplers carbonyl cyanide p-(trifluoromethoxy)phenylhydrazone, nigericin, gramicidin, valinomycin, and A 23187. Under similar conditions uncouplers stimulate the vesicle adenosinetriphosphatase (ATPase) by from 40 to 80%. ATP-sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(63 citation statements)
references
References 29 publications
(27 reference statements)
5
58
0
Order By: Relevance
“…Activation of this system increases intracellular sodium, which might suppress the neuronal activities. As another explanation, the synthesis of acetylcholine in the brain has been reported to be impaired even without decreases in ATP during mild hypoxia (GIBSON and BLASS, 1976), and ATP-supported uptake of acetylcholine by synaptic vesicles was found to be suppressed with pH levels remaining acidic (ANDERSON et al, 1982). The decrease in pH has also been shown to inhibit depolarization-induced Cat + entry in synaptosomes (NACHSHEN and BLAUSTEIN, 1979).…”
Section: Discussionmentioning
confidence: 98%
“…Activation of this system increases intracellular sodium, which might suppress the neuronal activities. As another explanation, the synthesis of acetylcholine in the brain has been reported to be impaired even without decreases in ATP during mild hypoxia (GIBSON and BLASS, 1976), and ATP-supported uptake of acetylcholine by synaptic vesicles was found to be suppressed with pH levels remaining acidic (ANDERSON et al, 1982). The decrease in pH has also been shown to inhibit depolarization-induced Cat + entry in synaptosomes (NACHSHEN and BLAUSTEIN, 1979).…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that the vesicular GABA uptake and glycine uptake are both driven by an electrochemical proton gradient, generated by a proton-pump ATPase in the synaptic vesicle membrane. Thus, the nature of the driving force for the vesicular uptake of the inhibitory amino acid neurotransmitters is likely to be very similar to that involved (i) in the vesicular uptake of glutamate (11,12), (ii) in catecholamine uptake into chromaffin granules (22,23) and brain synaptic vesicles (29), or (iii) in acetylcholine uptake into Torpedo synaptic vesicles (30). In contrast, other amino acids such as phenylalanine, leucine, histidine, and proline showed no ATP-dependent uptake into synaptic vesicles prepared from the cerebrum (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Proton-translocating ATPases have also been described in a number of intracellular organelles (Anderson et al, 1982;Hutton, 1982;Dean et al, 1984;Forgac et al, 1983;Galloway et al, 1983;Glickman et al, 1983). Intracellular vesicles with proton pumps fuse with and form from the plasma membrane, and it has been suggested that H+ pumps may participate in cellular pH regulation (Adelsberg & Al-Awqati, 1986).…”
Section: H+-translocating Atpasesmentioning
confidence: 99%